2018
DOI: 10.1371/journal.pbio.2005769
|View full text |Cite
|
Sign up to set email alerts
|

Blindsight relies on a functional connection between hMT+ and the lateral geniculate nucleus, not the pulvinar

Abstract: When the primary visual cortex (V1) is damaged, the principal visual pathway is lost, causing a loss of vision in the opposite visual field. While conscious vision is impaired, patients can still respond to certain images; this is known as ‘blindsight’. Recently, a direct anatomical connection between the lateral geniculate nucleus (LGN) and human motion area hMT+ has been implicated in blindsight. However, a functional connection between these structures has not been demonstrated. We quantified functional MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 76 publications
(97 reference statements)
4
58
3
Order By: Relevance
“…LGd inactivation in VISp lesioned mice has been shown to reduce extrastriate activity and eliminate blindsight behavior (Schmid et al, ). Human imaging studies have suggested that LGd projections to extrastriate area MT are the critical anatomical substrate to blindsight (Ajina et al, ; Ajina & Bridge, ; Sincich et al, ). Area MT in humans (also known as V5 in primates) is part of the dorsal visual‐processing stream and plays an important role in motion perception as MT neurons are tuned to the speed and direction of moving visual stimuli (Born & Bradley, ).…”
Section: Discussionmentioning
confidence: 99%
“…LGd inactivation in VISp lesioned mice has been shown to reduce extrastriate activity and eliminate blindsight behavior (Schmid et al, ). Human imaging studies have suggested that LGd projections to extrastriate area MT are the critical anatomical substrate to blindsight (Ajina et al, ; Ajina & Bridge, ; Sincich et al, ). Area MT in humans (also known as V5 in primates) is part of the dorsal visual‐processing stream and plays an important role in motion perception as MT neurons are tuned to the speed and direction of moving visual stimuli (Born & Bradley, ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of a role for the LGN, there are reports of enhanced structural connectivity 180 and functional connectivity 181 between the LGN and V5 in patients who are cortically blind who have motion-related blindsight, whereas connectivity between the pulvinar and V5 is the same irrespective of whether or not a patient has blindsight 181 . Furthermore, residual neurons within the macaque LGN (which becomes profoundly degenerated after V1 lesions) transmit visual information to V5 that support preserved visual abilities 92 , regardless of in which life stage a V1 lesion is incurred 165 .…”
Section: Box 2 | Subcortical Contributions To Blindsightmentioning
confidence: 99%
“…We also anticipate that blindsight function will depend upon the underlying visual structures. Therefore, patients demonstrating blindsight for trustworthiness and dominance traits here may not necessarily have shown motion blindsight on previous studies and vice versa (13)(14)(15). This has potential implications for clinical practice, as blindsight may offer a mechanism for training and rehabilitation after V1 damage.…”
Section: Introductionmentioning
confidence: 82%
“…This was defined as achieving either an average score, or a score for individual conditions that was significantly above chance, using a statistical threshold of p < 0.05 and a cumulative binomial distribution. This was an identical method to our previous work, except that the stimulus was a face rather than a drifting Gabor (15) or moving dots (13). The critical point was that patients performed above chance despite absent visual capacity in the targeted region of the visual field according to Perimetry (Figure 1).…”
Section: Blindsight Definitionmentioning
confidence: 98%